Effect of plant spacing on growth, yield and fruit quality of some introduced banana (Musa AAA) clones - Elkashif, Mohamed; Elamin, O. M.; Hag Ahmed, L. H. (Gezira Journal of Agricultural Science; Vol 13 No 2 (2015), 2015)
A field experiment was conducted at the Experimental Farm of the National Institute for the Promotion of Horticultural Exports, University of Gezira, Sudan, during 2009/10 and 2010/11. The objective of the study was to determine the effects of plant spacing on the vegetative growth, crop earliness, yield components, total yield and fruit quality of  five introduced banana clones under Gezira conditions, Sudan. Treatments consisted of three banana clones introduced from Austria, namely, Williams hybrid 172 (WH 172), Williams hybrid 1366 (WH 1366) and Grand Nain 1824 (GN 1824) and two clones introduced from South Africa, namely, Zelig and Bio. These five introduced clones were compared with the local clone Dwarf Cavendish (DC). Plant spacing was 2x2, 2x3 and 3x3 m. Treatments were arranged in a split plot design with three replicates. Plant spacing was assigned to the main plots and clones to the subplots. Results showed that vegetative growth parameters, yield and yield components were significantly affected by banana clones and plant spacing. Generally, the introduced banana clones had more vigorous vegetative growth than the local clone DC. The most vigorous vegetative growth was obtained by WH 172 followed by WH 1366 and GN 1824. Plant spacing of 2x3 m and 3x3 m resulted in significantly higher growth parameters values than 2x2 m. The earliest clone was GN 1824 and the latest were Bio and DC. Bio clone took the longest time from shooting to harvesting and both WH clones and Zelig  took the shortest. Plant spacing of 3x3 m resulted in significantly the shortest time from shooting to harvesting compared to the others. The highest yield and yield components were obtained by WH 172, WH 1366 and GN 1824 and the lowest were obtained by the local clone DC. Plant spacing of 3x3 m resulted in the highest yield components but the lowest total yield However, the close spacing of 2x2 m produced the lowest yield components but the highest total yield due to the large number of bunches per unit area. Total soluble solids were comparable in all clones, however, GN 1824 and WH 1366 had a better taste than the other clones. Plant spacing of 2x3 m and 3x3 m resulted in significantly higher TSS and taste values than 2x2 m. It is recommended to grow the banana introduced clones WH 172, WH 1366 and GN 1824 at a spacing of 2X3 m for the highest yield and best fruit quality.      أجريت التجارب بحقل بحوث المعهد القومي لتنمية الصادرات البستانية، جامعة الجزيرة، في الفترة من  2009 الي 2011. الهدف من الدراسة هو معرفة أثر مسافات الزراعة على النمو الخضري والتبكير ومكونات الإنتاج والإنتاجية ونوعية الثمار لخمسة أصناف من الموز مستجلبة من خارج السودان ، تحت ظروف الجزيرة بالسودان. اشتملت المعاملات على ثلاث سلالات من الموز مستوردة من النمسا وهي هجين الوليامز 172 (WH172) وهجين الوليامز 1366 (WH1366) وجراندنين 1824 (GN1824) وسلالتين استجلبتا من جنوب أفريقيا وهما زيلج وبايو. هذه السلالات الخمس المستجلبة من الخارج ثم تقويمها بالمقارنة مع السلالة المحلية الكافندش القزم (DC). مسافات الزراعة كانت 2 × 2م و 2 × 3م و 3×3م . نظمت المعاملات في تصميم القطع المنشقة بثلاث مكررات. اعتبرت مسافات الزراعة قطعاً رئيسية والسلالات قطعاً ثانوية. أظهرت النتائج أن تأثير السلالات ومسافات الزراعة كان معنوياً على النمو الخضري ومكونات الإنتاج والإنتاجية ونوعية الثمار. عموماً السلالات المستجلبة من الخارج أظهرت نمواً خضرياً أفضل من السلالة المحلية DC. أعطت السلالات WH172, و WH1366 وGN1824 نمواً خضرياً افضل من غيرها. مسافات الزراعة 2×3م و 3×3م أعطت نمواً خضرياً أفضل من 2×2م. أكثر السلالات تبكيراً هي  GN1824 وأكثرها تأخراً هي بايو وDC. استغرقت السلالة بايو زمناً أطول من الإزهار وحتى الحصاد أما السلالات WH172 وWH1366 وزيلج استغرقت وقتاً أقصر. مسافات الزراعة 3×3م نتج عنها زمناً أقصر من الإزهار وحتى الحصاد. السلالات WH172 وWH1366 وGN1824 أعطت أعلى إنتاجية بينما اعطت السلالة المحلية DC أقل إنتاجية. مسافات الزراعة 3×3م اعطت أعلى مكونات الإنتاج وأقل إنتاج كلي بينما أعطت مسافات الزراعة 2×2م أقل مكونات الإنتاج وأعلى إنتاج كلي نسبة للعدد الكبير من السبائط في وحدة المساحة. المواد الصلبة الذائبة الكلية كانت متقاربة في كل السلالات ولكن السلالات GN1824  و WH1366 أعطت  مذاقاً  أفضل من غيرها. مسافات الزراعة 2×3م و3×3م أعطت أعلى محتوى من المواد الصلبة الذائبة الكلية وافضل مذاق بالمقارنة مع  2x2 م. يوصى بزراعة  السلالات WH172  وWH1366 وGN1824 بمسافات  2×3م للحصول على أعلى انتاجية من الثمار ذات الجودة العالية.